Implementation Of Information Services with The Approach to Cognitive Behavior Therapy to Improve Learning Independence at SMP Negeri 1 Sidamanik - Saragih, Ema Aulia; Jamila, Jamila (Jurnal Riset Ilmu Pendidikan, 2023)
This study aims to determine the implementation of information services using the cognitive behavior therapy approach to increase learning independence at SMP Negeri 1 Sidamanik. The subjects in this study were counseling teachers, subject teachers and students in class IX, while the objects in this study were 15 students in class IX-F at SMP Negeri 1 Sidamanik, who experienced problems with lack of independent learning. Implementation of the service is carried out in two times the provision of information services. This research is qualitative research and to obtain data and information in this study, observations and interviews were carried out. The data analysis techniques used were data reduction, data presentation and drawing conclusions. Based on the results of research by applying information services with the Cognitive Behavior Therapy approach, it can increase learning independence